Molecular Imprinting for High-Added Value Metals: An Overview of Recent Environmental Applications - George Z. Kyzas; Dimitrios N. Bikiaris (Advances in Materials Science and Engineering)
One of the most hot topics of recent research is the reuse of some compounds existing as pollutants in environment. These compounds (molecules, ions, complexes, etc.) are of high-added value and it will be ideal to selectively bind them with any environmental application and reuse them in their initial or modified form. The latter can be achieved using molecular imprinting. In the present review article, an overview of the recent attempts for the selective binding of some precious metals (i.e., gold, silver, and platinum) of high-added value is done using molecular imprinted polymers (MIPs) as materials. The simplicity of their use, their relatively low cost, and the broad range of possible guest molecules (small organic molecules, ions, metals, and also biological macromolecules) have since led to the important development of molecular imprinting.